“Just Got Diagnosed; What Worked for You?”: A Mixed-Methods Analysis of Treatment Experiences in the Prolactinoma Subreddit - Dimitroyannis, Rose; Fenton, David; Thodupunoori, Sharanya; Cho, Stella; Nordgren, Rachel; Polster, Sean P.; Horowitz, Peleg M.; Das, Paramita; Roxbury, Christopher R. (Journal of Neurological Surgery Part B: Skull Base, 2024)
Introduction With improvement in complication and remission rates, recent studies have suggested the viability of transsphenoidal surgery as first-line management for prolactinomas. Reddit, an online forum, allows posters to interact with one another, and discuss symptoms, treatments, and disease courses through specialized forums known as “subreddits.” Given the lack of research comparing patient experience on pharmacotherapy versus surgery, we sought to assess the sentiment of treatment within the “r/Prolactinoma subreddit” community.Methods A search was done by filtering the r/Prolactinoma subreddit. Posts were sorted by “top” of “all time,” meaning entries with the most engagement throughout the site's history. Welch's t-test was used to analyze treatment type, while sentiment regarding treatment was analyzed using grounded theory qualitative methods.Results From 189 total entries, 82 were included; 33% (n = 27/82) were posts. Of posters disclosing their treatment, 11% underwent surgery (n = 9/79), while 76% received medication (n = 60/79). The proportion of positive:negative sentiment and level of engagement on posts regarding pharmacotherapy versus surgical treatments were not significantly different (p > 0.05). Qualitative analysis showed themes of changes after medical treatment, immediate changes postsurgery, and online community.Conclusion Our mixed-methods study found statistically nonsignificant differences in sentiment when comparing Reddit posts from patients who underwent medical and surgical management. Qualitative analysis revealed several themes regarding patients' perceptions of medical and surgical management and the benefits of an online community. The qualitative themes brought to light by this study may serve to inform future studies examining the patient experience with prolactinoma care.
Keywords: prolactinoma; social media; sentiment analysis; reddit